2014
DOI: 10.2166/wh.2014.115
|View full text |Cite
|
Sign up to set email alerts
|

Water-related factors and childhood diarrhoea in African informal settlements. A cross-sectional study in Ouagadougou (Burkina Faso)

Abstract: Improved access to water is a key factor in reducing diarrhoeal diseases, a leading cause of death among children in sub-Saharan Africa. In terms of water access, sub-Saharan African cities are some of the worst off in the world, with 20% of populations supplied by an unimproved water source. This situation is even worse in informal settlement areas. Using cross-sectional data on access to water from a survey implemented in three informal neighbourhoods of the Ouagadougou Health and Demographic Surveillance Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 19 publications
2
27
1
Order By: Relevance
“…All other included studies used binary water variables in the analysis to compare households with on-plot and off-plot water supplies; some specified the water source types. Five studies investigated household use of multiple water sources; one reported exclusive use of the on-plot water source (Devoto et al, 2011), one reported rainwater as an alternative source (Dos Santos et al, 2015), and three reported use of multiple on-and off-plot sources (Brown et al, 2013;Henry, 1981;Wang et al, 1989).…”
Section: Type Of Water Sourcementioning
confidence: 99%
See 4 more Smart Citations
“…All other included studies used binary water variables in the analysis to compare households with on-plot and off-plot water supplies; some specified the water source types. Five studies investigated household use of multiple water sources; one reported exclusive use of the on-plot water source (Devoto et al, 2011), one reported rainwater as an alternative source (Dos Santos et al, 2015), and three reported use of multiple on-and off-plot sources (Brown et al, 2013;Henry, 1981;Wang et al, 1989).…”
Section: Type Of Water Sourcementioning
confidence: 99%
“…[ Figure 4] Among the ten rigorous studies on self-reported diarrhea, five studies found a significant association between on-plot water supplies and lower risk of diarrhea (Brown et al, 2013;Bukenya et al, 1991;Dos Santos et al, 2015;Molbak et al, 1997;van der Hoek et al, 2001). Households in Vietnam with on-plot water supplies had significantly lower longitudinal diarrhea prevalence than households with access to improved sources off plot (longitudinal prevalence ratio (LPR)=0.59, 95% CI: 0.39-0.91 (p=0.018)) (Brown et al, 2013).…”
Section: Diarrheal Diseasesmentioning
confidence: 99%
See 3 more Smart Citations